Enablers and barriers to implementation of and compliance with school-based healthy food and beverage policies: a systematic literature review and meta-synthesis. Issue 15 (22nd October 2020) - Ronto, R.; Rathi, N.; Worsley, A.; Sanders, T.; Lonsdale, C.; Wolfenden, L.
Abstract: Objective: Schools have been recognised as a potential setting for improving young peoples' food and beverage choices; however, many schools fail to adhere to healthy food and beverage policy standards. The current study aimed to explore the enablers and barriers to effective implementation of and compliance with school-based food and beverage policies. Design: Systematic review and meta-synthesis. Eight electronic databases were searched for articles in June 2019. Studies were eligible for inclusion if they reported on implementation and/or compliance of school-based food and/or beverage policies with outcomes relating to enablers and/or barriers. This review had no restrictions on study design, year of publication or language. Seventy-two full-text articles were assessed for eligibility, of which twenty-eight were included in this review. Setting: Studies conducted globally that focused on schools. Participants: School-based healthy food and beverage policies. Results: Financial (cost of policy-compliant foods, decreased profit and revenue), physical (availability of policy-compliant foods, close geographical proximity to unhealthy food outlets) and social (poor knowledge, understanding, and negative stakeholders' attitudes towards policy) factors were the most frequently reported barriers for policy implementation. Sufficient funding, effective policy communication and management, and positive stakeholders' attitudes were the most frequently reported enablers for policy implementation. Conclusions: There is a need for better communication strategies, financial and social support prior to school-based food policy implementation. Findings of this review contribute to a thorough understanding of factors that underpin best practice recommendations for the implementation of school-based food policy, and inform those responsible for improving public health nutrition.